2009
DOI: 10.1097/mnm.0b013e32832ee09d
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: prevalence of malignant incidental thyroid nodules identified on fluorine-18 fluorodeoxyglucose positron emission tomography

Abstract: The high prevalence of malignancy associated with focal hypermetabolic thyroid nodules found on F-FDG-PET warrants further evaluation when detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
1
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 31 publications
5
67
1
10
Order By: Relevance
“…For the FDG uptake pattern, numerous studies found that the malignancy rate for the focal FDG uptake pattern was in the range of 14.0%-68.8% (Table 1). A recent systematic review of Ͼ55,000 patients reported a malignancy risk of 33.2% for focal FDG uptake lesions [19]. Kang et al [20] compared the malignancy rate between the focal and diffuse uptake patterns and found that the focal uptake group had a significantly higher rate than the diffuse uptake group (37.2% versus 4.7%).…”
Section: Significance Of Fdg-pet-detected Thyroid Incidentalomas and mentioning
confidence: 99%
“…For the FDG uptake pattern, numerous studies found that the malignancy rate for the focal FDG uptake pattern was in the range of 14.0%-68.8% (Table 1). A recent systematic review of Ͼ55,000 patients reported a malignancy risk of 33.2% for focal FDG uptake lesions [19]. Kang et al [20] compared the malignancy rate between the focal and diffuse uptake patterns and found that the focal uptake group had a significantly higher rate than the diffuse uptake group (37.2% versus 4.7%).…”
Section: Significance Of Fdg-pet-detected Thyroid Incidentalomas and mentioning
confidence: 99%
“…The reason for this wide range might be variability of the population characteristics and background risk of thyroid disease related to geographic area (Bertagna et al 2013). The high risk of malignancy in incidentalomas warrants further evaluation when detected (Shie et al 2009), which might be explained in two ways. First, as increased FDG uptake indicates either accelerated production of GLUT or enhanced glycolysis related to malignancy, incidentalomas detected by PET might have a higher risk of malignancy (Van den Bruel et al 2002).…”
Section: Incidentalomas Detected By Fdg Petmentioning
confidence: 99%
“…The PET positive thyroid abnormalities that are associated with an increased risk of thyroid malignancy include focal lesions, unilateral involvement and a palpable nodule on clinical examination 2,3 . This patient displayed all of these features.…”
Section: Discussionmentioning
confidence: 63%